NALISIS REPLIKASI PROGRAM PENANGGULANGAN KEMISKINAN MANDIRI PERKOTAAN - Dede Ruslan (Quantitative Economics Journal, 2015)
PNPM urban areas, is one of the programs implemented to address the problem for the poverty in the city of Medan. On the other hand, the Medan City Government task and function in terms of governance and service to the community. Medan city government administration as a subsystem of state government intended to increase the efficiency and effectiveness of governance and public service. In this paper uses methodologi of research with replication paradigm formulated to clarify the terminology and functions. Paradigm consists of four main types of replication, the retesting (retest), internal, independent, and theoretical. Our findings show that PNPM Urban general in Medan has been carrying out his duties as well as possible to achieve the program's objectives, namely increasing prosperity and employment opportunities of the poor independently. So Pemko field needs to appreciate the Poverty Reduction program conducted jointly by the PNPM Urban. Therefore Medan City Government is expected to continue to support PNPM Urban program to resume some previous policies and alignment with the results of the evaluation and field conditions. As a token of appreciation Pemko field against Poverty Program conducted by PNPM Urban Terrain pemko need to replicate the program PNPM Urban in poverty reduction as outlined in the remainder of the Regional Poverty Reduction Strategy.